2005
DOI: 10.1039/b505278p
|View full text |Cite
|
Sign up to set email alerts
|

First osmium-catalysed ketamination of alkenes

Abstract: Conditions for a first oxidative conversion of alkenes into 2-amino ketones are described, which yield racemic products within a direct oxidation pathway and 2-amino ketones with up to 99% enantiomeric excess from the corresponding enantiopure amino alcohols.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…In the course of optimization studies (Table , entries 5 and 7), the generation of imidazo[1,2- a ]­pyridine-3-carbaldehyde 3a was observed via intramolecular aminooxygenation. , In view of the importance of this derivative, ,, we decided to investigate the reaction further. Screening of silver salts, ligands, and other parameters, such as solvent, temperature, atmosphere, etc., were undertaken, and the data are summarized in Table S1 (see Supporting Information).…”
mentioning
confidence: 99%
“…In the course of optimization studies (Table , entries 5 and 7), the generation of imidazo[1,2- a ]­pyridine-3-carbaldehyde 3a was observed via intramolecular aminooxygenation. , In view of the importance of this derivative, ,, we decided to investigate the reaction further. Screening of silver salts, ligands, and other parameters, such as solvent, temperature, atmosphere, etc., were undertaken, and the data are summarized in Table S1 (see Supporting Information).…”
mentioning
confidence: 99%
“…This compound has been reported . This compound was prepared following the general procedure D using 2-oxo-1,2-diphenylethan-1-aminium hydrochloride (0.500 g, 2.02 mmol, 1.0 equiv) in DCM (10 mL), triethylamine (0.816 g, 1.12 mL, 8.08 mmol, 4.0 equiv) and mesyl chloride (0.348 g, 3.03 mmol, 1.5 equiv) in DCM (10 mL), water (50 mL) to quench, and DCM (2 × 25 mL) for extraction to generate the crude product, which was purified by column chromatography (30% EtOAc in petroleum ether (40–60)) to give the product as a white solid (0.310 g, 1.07 mmol, 52.9%).…”
Section: Methodsmentioning
confidence: 99%
“…This compound has been reported. 35 This compound was prepared following the general procedure D using 2-oxo-1,2diphenylethan-1-aminium hydrochloride (0.500 g, 2.02 mmol, 1.0 equiv) in DCM (10 mL), triethylamine (0.816 g, 1.12 mL, 8.08 mmol, 4.0 equiv) and mesyl chloride (0.348 g, 3.03 mmol, 1.5 equiv) in DCM (10 mL), water (50 mL) to quench, and DCM (2 × 25 mL) for extraction to generate the crude product, which was purified by column chromatography (30% EtOAc in petroleum ether (40−60)) to give the product as a white solid (0.310 g, 1.07 mmol, 52.9%). TLC: R f ca 0.3 (7:3, hexane:EtOAc), strong UV-active; HRMS (ESI): found [M + Na] + 312.0696, C 15 H 15 NNaO 3 S requires [M + Na] + 312.0665 (error 0.7 ppm); υ max 3242,1687,1313,1293,1247,994,731, 508 cm −1 ; 1 H NMR (CDCl 3 , 400 MHz): δ 7.93 (d, 2H, J = 7.3 Hz), 7.53 (t, 1H, J = 7.4 Hz), 7.42−7.24 (m, 7H), 6.13 (d, 1H, J = 6.4 Hz), 6.07 (d, 1H, J = 6.2 Hz), 2.58 (s, 3H); 13 C{ 1 H} NMR (CDCl 3 , 101 MHz): δ 194.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…59 In further studies from the same group, it has been shown that carrying out aminohydroxylation under typical Sharpless conditions but with the omission of the chiral ligand can lead to the a-ketoamine, rather than the aminoalcohol, being the major reaction product (Scheme 9). 60 Enantiomerically enriched aminoalcohols can be converted to enantiomerically enriched a-aminoketones using similar conditions. A related observation comes from Zhu's attempts to optimise the aminohydroxylation of cinnamate esters, in which the a,a-diaminoarylketone was observed as a byproduct, 61 presumably arising by a second aminohydroxylation reaction on the enol form of the a-aminoketone, itself formed from the initial aminoalcohol by analogy to Muniz's studies.…”
Section: Alkene Aminohydroxylation and Diaminationmentioning
confidence: 99%